The Influence of Sustainable Human Resource Management Practices on Organizational Performance with Knowledge Management and Work Engagement as Mediation - Yuswardi, Yuswardi; Mon, Muhammad Donal; Liu, Lisa Carline (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
Human resources are one of the assets in an organization that can move other resources. In the current era of globalization, the problem is the difficulty of determining sustainable human resources are capable, and have good performance, until now it can be said that the quality of human resources in Indonesia is still relatively low. Data from respondents were collected by distributing questionnaires to 379 participants. This study employs the partial least squares - structural equation modeling method. The influence of sustainable human resource management practice on knowledge management is accepted, the effect of sustainable human resource management practices on work engagement is accepted, the effect of sustainable human resource management practice on organizational performance is not accepted, the effect of knowledge management on organizational performance is accepted, The effect of work engagement on organizational performance is accepted, the effect of knowledge management on work engagement is accepted, the effect of sustainable human resource management practice on organizational performance mediated by knowledge management is accepted, the effect of sustainable human resource management practice on organizational performance mediated by work engagement is accepted, and the effect of sustainable human resource management practice on work engagement mediated by knowledge management is accepted.